Corporate Sustainability disclosures and perfomance of Top 40 JSE Listed companies - Moyane, Motleke Virginia (University of the Witwatersrand, Johannesburg, 2023)
Corporate sustainability reports are typically included as part of integrated annual reports, because they explain to stakeholders how the organisation creates value over time” (IIRC, 2013). Literature posits that being a good corporate citizen is smart business and relevant for companies to report on how they affected the lives of communities in which they operate (King & Lessidrenska, 2009). This study assessed whether corporate sustainability reporting (evidenced through ESG components) affects the financial performance (ROA, ROE, ROI and Tobin’s Q) of JSE Top 40 companies. The study was quantitative in nature and took on characteristics of an event study which saw the collection of panel data on the JSE Top 40 companies over the period from 2017 to 2021. The data comprised of individualised ESG scores as determined through the Bloomberg ESG scoring matrix, together with reported financial performance measures over the period. The dependant variable for this study are the financial performance measures whilst the ESG scores are independent. From a statistical perspective, the results of the study indicate mixed reactions. The results for environmental factors indicate a positive correlation to all performance measures and that the relationship to performance is statistically significant, suggesting that businesses might increase their financial performance by funding environmental initiatives. For social factors, results indicate a negative correlation to ROA, ROE and ROI whilst there is no correlation to Tobin’s Q. Social indicators typically represent human obligations and such negative correlations imply that spending on this area may not yield positive financial returns but may yield better outcomes when considered against other intrinsic measures. The relationship between governance disclosures indicates positive correlations to ROA, ROE and ROI but negative for Tobin’s Q whilst the relationship between governance and performance appears to be largely positive and significant, save for Tobin’s Q which was negative and not statistically significant, thus proving that issues of effective corporate governance have a positive effect on financial performance. It is hoped that this research will help focus organisational efforts on issues of sustainability activities by providing broad categories on which ESG factors to focus on in 7 order to yield more financial performance whilst also contributing to the body of work on corporate sustainability reporting and the effect this has on financial performan
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Corporate Sustainability Reporting; Financial Performance; Return on Assets; Return on Investments; Return on Equity; Tobin’s Q; UCTD; SDG-8: Decent work and economic growth